STUDYING THE HUMAN SCALE AND PROPORTIONALITY OF MOSQUE BUILDINGS: SOME SELECTED CASE STUDIES IN ERBIL CITY - Mustafa, Faris Ali; Rashid, Saya Jamal (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2019)
Human scale and proportion have an important role in building design as they provide and create aesthetics and sense of place. In architecture, the human scale and proportion are based on the dimensions and proportions of the human body. The mosque is an important institution of Islam and is considered as a symbol of Islamic architecture. Also, it is a place of spiritual connection with God. This study aimed at addressing whether the human scale and proportionality have been used in mosques in the past and present. The objective of this research is to show if mosques in Erbil city built in different periods were concentrated on human scale and proportion to achieve aesthetic and comfort inside its prayer halls. To achieve it, three cases (the Great Mosque of Erbil Citadel, Rashad Mufty Mosque, and Madina Mnawara Mosque) were selected. The golden ratio was used as a technique method to measure and to see if the human scale and proportion were applied. From the three selected mosques, results show that none of them used the golden ratio completely in their designs. The highest value of golden ratio was achieved in the prayer hall of Rashad Mufty mosque with (82%) and the Great Mosque of Erbil citadel with (74%) consequently, while only 61% of the golden ratio was achieved in Madina Mnawara mosque. This study prompts the new generation of architects in Erbil city to consider human scale and proportionality through the application of a certain method, such as the golden ratio in the design of buildings in general and mosque buildings in particular.Â